주파수경매의 효율성 향상방안: 배분적 외부성이 존재하는 경우를 중심으로 - 양용현 (13866, 2014)
Auction is widely used in allocation and procurement of resources due to its desirable properties: efficiency and revenue maximization. It is well- known, however, that auction may fail to achieve efficiency when allocative externalities exist. Such a res